Expressing Humor in Audiovisual Translation From Bulgarian Into Russian - Stepanova, Maria (Media and Language, 2020)
The study considers the humour recreation for audiovisual translation of movies and TV series from Bulgarian into Russian. Translating humour in audiovisual content is a real challenge since while there are obvious linguistic similarities, the speech usage of the target audiences, the visual content perception, and the cultural background are different. Studying the translation of comical content in cognate languages should consider the cultural context and ensure an identical visual content perception by the target audience.